Atomic-Scale Friction on Crystal Surfaces in Ultra-High Vacuum - Song, Yiming; Maier, Sabine; Gnecco, Enrico; Meyer, Ernst (Springer Science and Business Media Deutschland GmbH, 2024)
This chapter reviews friction force microscopy investigations on single-asperity sliding contacts in ultra-high vacuum (UHV). The atomic-scale stick–slip observed under such conditions can be converted into a superlubric regime of motion by reducing the normal load and/or applying ultrasonic vibrations. Thermal vibrations and sliding direction (on a crystal surface) also influence the friction. The empirical Prandtl-Tomlinson (PT) model is introduced, which explains well the main experimental observations. The scenario is more complicated on two-dimensional (2D) materials, where the puckering effect explains the difference in friction observed on monolayers versus multiple layers. The moiré patterns formed on them are also influenced by elastic deformation, which can lead to significantly larger dissipation than that due to atomic stick–slip alone.
CRIS-Team Scopus Importer:2024-09-13